NOD2 Loss-of-Function Mutations and Risks of Necrotizing Enterocolitis or Focal Intestinal Perforation in Very Low-birth-weight Infants. Issue 2 (11th January 2016) - Härtel, Christoph; Hartz, Annika; Pagel, Julia; Rupp, Jan; Stein, Anja; Kribs, Angela; Müller, Andreas; Haase, Roland; Gille, Christian; Böttger, Ralf; Kittel, Jochen; Jensen, Reinhard; et al.
Abstract : Background: NOD2 loss-of-function mutations, that is, R702W [rs2066844], G908R [rs2066845], and Leu1007fsinsC [rs5743293], have been linked to inflammatory bowel diseases. It is yet unknown whether these variants are also associated with necrotizing enterocolitis (NEC) or focal intestinal perforation (FIP) in infants of very low birth weight (VLBW). Methods: To test this hypothesis, we genotyped 9082 VLBW infants with European ancestry enrolled in a prospective, population-based cohort study of the German Neonatal Network. We assessed the effect of the NOD2 gene variants on the risk for major morbidities of the gastrointestinal tract, that is, NEC/FIP requiring surgery in multivariable logistic regression analyses. Results: In the whole cohort of VLBW infants, carriers of ≥2 NOD2 variant alleles had an increased risk for NEC requiring surgery (odds ratio [OR], 3.57; 95% confidence interval [CI], 1.27–10.04; P = 0.03) and NEC or FIP requiring surgery (OR, 3.81; 95% CI, 1.70–8.51; P = 0.004) as compared with wild-type genotypes. In a multivariable logistic regression analysis including gestational age, birth weight, gender, multiple birth, and inborn delivery, the association between ≥2 NOD2 variant alleles and NEC surgery (OR, 4.14; 95% CI, 1.41–12.12; P = 0.009), FIP surgery (OR, 3.50; 95% CI, 1.02–12.04; P = 0.047), and NEC or FIP surgery (OR, 4.10; 95% CI, 1.74–9.73; P = 0.001) proved to be independent. We also performed a regression analysis in the subgroup of infants with available information on Lactobacillus acidophilus / Bifidobacterium infantis probiotic supplementation (n = 3638). Although probiotics had a protective effect on NEC and NEC or FIP requiring surgery, the NOD2 variants had no significant impact in this subgroup. Conclusions: VLBW infants carrying ≥2 NOD2 genetic risk factors of inflammatory bowel disease in adults have an increased risk for severe gastrointestinal complications, such as NEC requiring surgery. Therefore, infants might benefit from NOD2 genotyping followed by supplementation with probiotics. Replication studies are needed along with genome-wide arrays to allow risk-adapted prevention and therapeutic strategies.